Excursions in Harmonic Analysis, Volume 1 The February Fourier Talks at the Norbert Wiener Center - Andrews, Travis D.; Balan, Radu; Benedetto, John J.; Czaja, Wojciech; Okoudjou, Kasso A. (Applied and Numerical Harmonic Analysis,, 2013)
The Norbert Wiener Center for Harmonic Analysis and Applications provides a state-of-the art research venue for the broad emerging area of mathematical engineering in the context of harmonic analysis. This two-volume set consists of contributions from speakers at the February Fourier Talks (FFT) from 2006-2011. The FFT are organized by the Norbert Wiener Center in the Department of Mathematics at the University of Maryland, College Park. These volumes span a large spectrum of harmonic analysis and its applications. They are divided into the following parts: Volume I ·         Sampling Theory ·         Remote Sensing ·         Mathematics of Data Processing ·         Applications of Data Processing Volume II ·         Measure Theory ·         Filtering ·         Operator Theory ·         Biomathematics Each part provides state-of-the-art results, with contributions from an impressive array of mathematicians, engineers, and scientists in academia, industry, and government. Excursions in Harmonic Analysis: The February Fourier Talks at the Norbert Wiener Center is an excellent reference for graduate students, researchers, and professionals in pure and applied mathematics, engineering, and physics.